Literature Review: Analysis of Potential Human Error Factors in the Industrial Sector Using the Heart Method - Hasanuddin Hasanuddin; Husaini Husaini; Erida Wydiamala; Lenie Marlinae; Silvia Kristanti Tri Febriana (Indonesian Journal of Global Health Research, 2026)
Occupational Health and Safety (OHS) is a fundamental aspect of the industrial world, playing a crucial role in protecting workers and ensuring operational continuity. Various reports indicate that the majority of workplace accidents in industrial sectors, such as mining, construction, and manufacturing, are still dominated by human error. Therefore, a comprehensive evaluation of the probability of human error is necessary to reduce the number of workplace accidents and improve safety performance. Objective to analyze and integrate research findings related to the implementation of the Systematic Human Error Reduction and Prediction Approach (SHERPA) and Human Error Assessment and Reduction Technique (HEART) methods in identifying, measuring, and reducing the risk of human error in various industrial sectors. This study is a systematic literature review compiled according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Articles were searched through Google Scholar and PubMed databases using the keywords "Human Error," "Occupational Health and Safety (OHS)," "HEART," "Human Reliability Analysis," and "occupational accident." Inclusion criteria included articles published between 2021 and 2025, with full text, and discussing human error analysis using the HEART method in the industrial sector. Of the 313 identified articles, nine met the criteria and were analyzed qualitatively.  The HEART method produced varying Human Error Probability values, with the highest values for manual work in underground mining (0.89), manual valve operation in oil tank facilities (0.95), and cutting machine operation in the furniture industry (0.888). The dominant factors triggering errors included work fatigue, unclear instructions, time pressure, and lack of training. The HEART method is effective in providing a quantitative and holistic picture of human error risk.